ARCHAEOLOGICAL RESEARCH CARRIED OUT IN THE YEARS OF INDEPENDENCE ON THE BASIS OF THE ADOPTED LAWS AND REGULATIONS ON MATERIAL, CULTURAL AND ARCHAEOLOGICAL HERITAGE - Илауатдинов Р. К. (Web of Journals Publishing, 2025)
This article describes the research work and results of archaeological expeditions conducted in accordance with the laws, resolutions, and regulatory documents adopted by the government of the Republic of Uzbekistan for the development of archaeological science. It presents the scientific research and conclusions of prominent archaeologists in Karakalpak archaeology, as well as highlighting the attention given to archaeological science during the years of independence and the achievements in this field.
Keywords: Concept, Kuyuk Castle, G'. Khojaniyazov, expedition, Mizdakhkan monument.